Quantifying the accuracy and precision of a novel real-time 6 degree-of-freedom kilovoltage intrafraction monitoring (KIM) target tracking system. (23rd June 2017) - Kim, J-H; Nguyen, D T; Huang, C-Y; Fuangrod, T; Caillet, V; O'Brien, R; Poulsen, P; Booth, J; Keall, P
Abstract: Target rotation can considerably impact the delivered radiotherapy dose depending on the tumour shape. More accurate tumour pose during radiotherapy treatment can be acquired through tracking in 6 degrees-of-freedom (6 DoF) rather than in translation only. A novel real-time 6 DoF kilovoltage intrafraction monitoring (KIM) target tracking system has recently been developed. In this study, we experimentally evaluated the accuracy and precision of the 6 DoF KIM implementation. Real-time 6 DoF KIM motion measurements were compared against the ground truth motion retrospectively derived from kV/MV triangulation for a range of lung and prostate tumour motion trajectories as well as for various static poses using a phantom. The accuracy and precision of 6 DoF KIM were calculated as the mean and standard deviation of the differences between KIM and kV/MV triangulation for each DoF, respectively. We found that KIM is able to provide 6 DoF motion with sub-degree and sub-millimetre accuracy and precision for a range of realistic tumour motion.